Development Of A Steam-Based Homeostatic Module To Improve Students' Cognitive Abilities - Zico Fakhrur Rozi; Aceng Ruyani; Badeni (Postgraduate, University of Mataram, 2024)
This research aims to develop a STEAM-based homeostatic module to improve students' cognitive abilities. The subjects of this research were students of the Biology Education Study Program at PGRI Silampari University. In the learning process, students are given an assignment in the form of a project to test honje fruit extract (Etlingera hemisphaerica) as antihyperglycemia, antihypercholesterolemia and antihyperuricemia. Module development uses a 4D development model, with define, design, develop and disseminate stages. The instruments in the research are validation questionnaires for material experts, media experts, language experts, response questionnaires and evaluation test sheets. The research results showed that the module developed contained steam elements and was assessed as appropriate by material expert validators with a v-aiken value of 0.91, media experts 0.91 and language experts 0.88. Student responses to the module were 48.44 in the positive category. Students' cognitive abilities have increased with an N-gain value of 0.64 in the moderate increase category. Based on these results, it can be concluded that the STEAM-based homeostatic module is effective in improving students' cognitive abilities. The results of the analysis using the anova test showed that there were differences in the average learning outcomes between the experimental class and the control class.